Ambiguity and the interaction between the text and reader in Jurjani's theory from a phenomenological perspective - Zahra Delavar Abrebekooh; kobra roshanfekr; Isa Motaghizadeh; hamidreza shairi (دراسات فی اللغه العربیه و آدابها)
This study aims to examine Abd Al-Qahir Jurjani's theory from a phenomenological perspective. Because it can be acknowledged that his theory should be studied, not because it was the first in many respects, but because it is still working. It seems that this theory contains evidence of what the phenomenologists are currently searching for, especially with regard to the issue of interaction between the text and the reader, as well as the issue of ambiguity. The study relies on the descriptive-analytical method, using the views of phenomenologists such as Roman Ingarden and Wolfgang Iser. Among the results of this research, we can mention Abd al-Qahir's sharing with Ingarden about the importance of the reader's response to the text and the dialogue relationship between them, and his similarity with Iser in inviting the reader to actively participate and reconstruct the text.